Study of Sweating Rate and Morphometry of Sweat Gland in Kangayam Cattle during Different Environmental Conditions - Karumalaisamy, Devipriya; Palanisamy, Selvaraj; Santhanam, Jayachandran; Kattiannan, Balasundaram; Karuppusamy, Iniyah (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was conducted to evaluate sweating rate and the morphological changes of sweat gland of indigenous Kangayam cows during different climatic conditions. About six numbers of adult Kangayam cattle in the age range of 3 to 5 years were selected from farmer’s house in the vicinity of Namakkal and Sathyamangalam districts of Tamil Nadu. The skin biopsy samples were collected during winter (December – February) and summer (April- June) seasons. The sweating rate was calculated using a Cobalt Chloride Disk (CCD) method during both seasons. Histological measurements like, sweat gland length, sweat gland diameter, depth of sweat gland and sweat gland density were measured with the help of trinocular microscope (Leica DM 1000) with image analyzer (Leica application suit) software. The results revealed that the significant (P
Keywords: Environmental conditions; Kangayam; Morphometry; Sweat gland; Sweating rate